PENINGKATAN KOMPETENSI GURU MELALUI PELAKSANAAN SUPERVISI AKADEMIK DI TSANAWIYAH AL MA’ARIF KOTA BUKITTINGI - Wage Ummami (Jurnal Dedikasi Pendidikan, 2021)
Abstract: Academic supervision is an activity carried out by supervisors to improve teacher competence. The background of this research is based on the understanding of teachers in preparing lesson plans that are still low, besides that the ability of teachers to use learning methods and media is still not optimal so that the learning process has not run well. The purpose of this study was to improve teacher competence in preparing lesson plans through academic supervision. This research is a qualitative research, where data collection is done through observation and interviews with a number of informants such as the principal and teachers of Stanawiyah Al Ma' Arif Bukittinggi City. The process of qualitative data analysis and data validity was carried out by triangulation.